2006
DOI: 10.1007/s00234-006-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

Stent fracture in revascularization for symptomatic ostial vertebral artery stenosis

Abstract: PTAS for symptomatic ostial VA stenosis is effective in preventing recurrent stroke. As the open-cell single-joint type of stent is associated with the risk of fracture, long-term follow-up examinations including simple radiography are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…Some authors have also reported stent fracture as a complication of ostial VA stenosis, and stent fracture rates range from 5% to 50%. 13,20,21 Weber et al reported two fractures (5%) associated with restenosis. However, during a mean followup of 31.5 months, Tsutsumi et al reported three stent fractures (50%) detected in coronary stents deployed for symptomatic ostial VA stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have also reported stent fracture as a complication of ostial VA stenosis, and stent fracture rates range from 5% to 50%. 13,20,21 Weber et al reported two fractures (5%) associated with restenosis. However, during a mean followup of 31.5 months, Tsutsumi et al reported three stent fractures (50%) detected in coronary stents deployed for symptomatic ostial VA stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Endovascular treatment with balloon angioplasty alone yields unsatisfactory results due to elastic recoil, vessel dissection, and high restenosis rates. 5,6 Studies on stent placement of ostial vertebral artery lesions by using bare metal stents have reported excellent immediate results and low rates of periprocedural complications; however, mid-and longterm results remained disappointing due to issues of stent fracture caused by mechanical strain [7][8][9] and high rates of instent restenosis as a result of neointimal hyperplasia. 7,10,11 The use of drug-eluting coronary stents (DES) for the prevention of in-stent restenosis in ostial vertebral artery stenotic lesions has been advocated recently.…”
mentioning
confidence: 99%
“…16,20) However, stent fracture was reported to be associated with stent type, not vessel diameter, with the open-cell type of coronary stent exhibiting a high risk of fracture. 17) We used the present stent due to its closed-cell design, and its conformability and flexibility for tortuous vessels such as the renal artery, which was originally approved for the angioplasty.…”
Section: Discussionmentioning
confidence: 99%